Faith and Wisdom in Science - McLeish, Tom. (Oxford : Oxford University Press, 2014)
"Can you Count the Clouds?" asks the voice of God from the whirlwind in the stunningly beautiful catalogue of nature--questions from the Old Testament Book of Job. Tom McLeish takes a scientist's reading of this ancient text as a centrepiece to make the case for science as a deeply human and ancient activity, embedded in some of the oldest stories told about human desire to understand the natural world. Drawing on stories from the modern science of chaos and uncertainty alongside medieval, patristic, classical and Biblical sources, Faith and Wisdom in Science challenges much of the current 'science and religion' debate as operating with the wrong assumptions and in the wrong space.
Includes bibliographical references and index.
Keywords: Bible and science